2014
DOI: 10.5755/j01.eee.20.7.8017
|View full text |Cite
|
Sign up to set email alerts
|

Hexapod Robot Energy Consumption Dependence on Body Elevation and Step Height

Abstract: Walking robots are well known for being able to walk over rough terrain and adapt to various environments. Hexapod robots are chosen because of their better stability and higher number of different gaits. However, having to hold the whole weight of the body and a large number of actuators makes all walking robots less energetically efficient than wheeled machines. Special methods for energy consumption optimization must be found. In this paper, hexapod robot energy consumption dependence on body elevation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The students implement the proposed problem and the validation of the results is made on MATLAB® [2][3][4][5][6]8,14,[23][24][25]32,46]. In the example the development application was made with Matlab® GUI (Graphical User Interface) that had a virtual robot similar to MOTOMAN HP3L and slider buttons to change the internal coordinates of the robot links motors in order to allow the communication between the computer and the real robot.…”
Section: Matlab® For Robotic Researchmentioning
confidence: 99%
“…The students implement the proposed problem and the validation of the results is made on MATLAB® [2][3][4][5][6]8,14,[23][24][25]32,46]. In the example the development application was made with Matlab® GUI (Graphical User Interface) that had a virtual robot similar to MOTOMAN HP3L and slider buttons to change the internal coordinates of the robot links motors in order to allow the communication between the computer and the real robot.…”
Section: Matlab® For Robotic Researchmentioning
confidence: 99%
“…In our previous work, we have analysed energy consumption of a hexapod robot walking in an obstacle-free terrain [31]. Here, we address the problem of minimizing energy consumption of a hexapod robot while moving over a terrain with small-sized obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, there are many explorations on optimal control problems of hexapod robots. Sliva and Machado [8] reviewed optimization method used in legged robots; energy/power optimal control objective functions are listed out; Sanz-Merodio et al [9] explored energy consumption of mammal and insect type robots and concluded that leg 2 Mathematical Problems in Engineering dynamics accounts for most energy consumption; Chen et al [10] designed an insect type hexapod robot and leg has a series mechanism type; the optimal control of leg swing is solved by pseudospectral method; Roy et al [11][12][13][14] explored kinematic dynamics and optimal control problems of hexapod robot; the hexapod robot is driven by electric motor, so it has a series mechanism type; Luneckas et al [15] analyzed hexapod robot's energy consumption by motion of body and step height; Deng et al [16] explored energy reducing problem of hexapod robot by kinematics analysis; Gonzalez de Santos et al [17] explored minimization of hexapod robot in irregular terrain; the optimal analysis is based on statically stable gait; Jin et al [18] explored hexapod walking robot's power consumption optimization problem by torque distribution algorithm and parameters include duty factor, stride length, bogy height, and foot trajectory lateral offset; Zhu et al [19] explored optimal design of hexapod robot with kinematic model.…”
Section: Introductionmentioning
confidence: 99%